CARACTERIZACIÓN DE CLITEMNESTRA Y GAMENÓN DE ESQUILO A SÉNECA - de Paco Serrano, Diana (Myrtia, 2003)
The author tries to prove that the musical terminology in Euripides' drama and the introduction in it of some new terms shows the changes of meaning in the most ancient terms. This analysis strenghtens Euripides' image as a musician advocate of the changes that took place in the music of his time.